A NeverEnding story: tracing the OECD's evolving narratives within a global development complex. (15th March 2021) - Auld, Euan; Morris, Paul
ABSTRACT: This paper applies insights from narrative theory to analyse the OECD's transition to providing humanitarian large-scale assessments under the SDGs, situating this within the evolving dynamics of a global development complex. The perspective is guided by the thematic interests of the special issue, with the goal of enriching understanding of both the OECD's changing positions and capacities in the global field, and the theories, ideas and styles of reasoning it has employed (as well as how they operate). The paper takes its starting point from recent scholarship in international relations (IR) that has applied narrative to the study of international organisations, highlighting the central role of strategic narratives in forging world order and in establishing organisational legitimacy. We describe the core narrative as akin to a Three Act Play (with five stages) which we use as a heuristic device to trace the entwined development stories of PISA and the advent of Humanitarian Assessment in international development.